The Implementation Of Character Education In State Polytechnic Of Balikpapan - Nawang Retno Dwiningrum; Basri Basri (JST (Jurnal Sains Terapan), 2016)
The purpose of this study is to describe and analyze the implementation of character education at the State Polytechnic of Balikpapan viewed from institution, academic / curricular and non-curricular.Type of this research is descriptive qualitative research. The data used in this study was purposive sampling, informant who serves as key informants in this study, such as:Director, Vice Director I, Vice Director II, and students. The data were analyzed by using Analysis Data on Interactive Model.The result of this character education implementation researchin StatePolytechnic of Balikpapan at the institution level there are no policies or regulations governing the implementation of educationcharacter in academic / curricular that was still included in the civicsand religion subject have not been integrated into all subjects, and in character education extracurricular had already implemented in student organizations